NGS Evaluation of Colorectal Cancer Reveals Interferon Gamma Dependent Expression of Immune Checkpoint Genes and Identification of Novel IFNγ Induced Genes - Xu, Lai; Pelosof, Lorraine; Wang, Rong; McFarland, Hugh I.; Wu, Wells W.; Phue, Je-Nie; Lee, Chun-Ting; Shen, Rong-Fong; Juhl, Hartmut; Wu, Lei-Hong; Alterovitz, Wei-Lun; Petricon, Emanuel; et al. (Frontiers in Immunology, 2020)
To evaluate the expression of immune checkpoint genes, their concordance with expression of IFNγ, and to identify potential novel ICP related genes (ICPRG) in colorectal cancer (CRC), the biological connectivity of 6 well documented (“classical”) ICPs (CTLA4, PD1, PDL1, Tim3, IDO1 and LAG3) with IFNγ and its coexpressed genes was examined by NGS in 79 CRC pairs. Identification of novel IFNγ- induced molecules with potential ICP activity was sought. In our study, the 6 classical ICPs were statistically upregulated and correlated with IFNγ, CD8A, CD8B, CD4 and 180 additional immunologically related genes in IFNγ positive (FPKM > 1) tumors. By ICP coexpression analysis, we also identified 3 IFNγ-induced genes [(IFNγ-inducible lysosomal thiol reductase (IFI30), guanylate binding protein1(GBP1) and guanylate binding protein 4 (GBP4)] as potential novel ICPRGs. These 3 genes were upregulated in tumor compared to normal tissues in IFNγ positive tumors, coexpressed with CD8A and had relatively high abundance (average FPKM = 362, 51, 25 respectively), compared to the abundance of the 5 well defined ICPs (Tim3, LAG3, PDL1, CTLA4, PD1; average FPKM = 10, 9, 6, 6, 2 respectively), although IDO1 is expressed at comparably high levels (FPKM=39). We extended our evaluation by querying the TCGA database which revealed the commonality of IFNγ dependent expression of the 3 potential ICPRGs in 638 CRCs, 103 skin cutaneous melanomas (SKCM), 1105 breast cancers (BC), 184 esophageal cancers (ESC), 416 stomach cancers (STC) and 501 lung squamous carcinomas (LUSC). In terms of prognosis, based on Pathology Atlas data, the correlation of GBP1 and GBP4, but not IFI30, with 5-year survival rate was positive in CRC, BC, SKCM and STC. Thus, further studies defining the role of IFI30, GBP1, and GBP4 in CRC are warranted.